2011
DOI: 10.1590/s0100-736x2011001200008
|View full text |Cite
|
Sign up to set email alerts
|

Pitiose em animais de produção no Pantanal Matogrossense

Abstract: Realizou-se, em quatro propriedades rurais no Pantanal Matogrossense, em 2009 e 2010, um estudo clínico e epidemiológico da pitiose em bovinos e equinos. A enfermidade ocorreu predominantemente entre os meses de novembro e março, correspondendo ao período chuvoso na região. A incidência média anual foi de 0,22% e 12,5% em bovinos e equinos, respectivamente. Nos bovinos, a distribuição dos casos ocorreu no ápice das cheias e restringiu-se a novilhas de 6 a 18 meses de idade, nas quais as lesões cutâneas estiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
5
18
0
14
Order By: Relevance
“…The clinical evaluation and the anatomopathological characterization of the lesions in the horses of the study, together with the histopathological results, confirmed the diagnosis of cutaneous pythiosis according to what was reported as a diagnostic method for equine pythiosis (3,5,10,(16)(17)(18)(19).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The clinical evaluation and the anatomopathological characterization of the lesions in the horses of the study, together with the histopathological results, confirmed the diagnosis of cutaneous pythiosis according to what was reported as a diagnostic method for equine pythiosis (3,5,10,(16)(17)(18)(19).…”
Section: Resultssupporting
confidence: 82%
“…La evaluación clínica y la caracterización anatomopatológica de las lesiones en los caballos del estudio, junto a los resultados histopatológicos confirmaron el diagnóstico de pythiosis cutánea de acuerdo con lo reportado como método diagnóstico de la pythiosis equina (3,5,10,(16)(17)(18)(19).…”
Section: Resultsunclassified
See 3 more Smart Citations